CD45RO+ Memory T Lymphocytes – a Candidate Marker for TNM-Immunoscore in Squamous Non-Small Cell Lung Cancer - Paulsen, Erna-Elise; Kilvær, Thomas Karsten; Rakaeekhanehkenari, Mehrdad; Johansen Maurseth, Ramona; Al-Saad, Samer; Hald, Sigurd; Al-Shibli, Khalid; Andersen, Sigve; Richardsen, Elin; Busund, Lill-Tove; Bremnes, Roy M.; Dønnem, Tom (Neoplasia, 2015)
Published version also available at http://dx.doi.org/10.1016/j.neo.2015.11.004 Tumor-infiltrating lymphocytes (TILs) are vital in limiting cancer progression and may supplement the TNM classification. CD45RO+ memory TILs show major prognostic impact in various malignancies but have not been extensively explored in non–small cell lung cancer (NSCLC). In this study, we aimed to evaluate their potential in a NSCLC TNM-Immunoscore. Tissue microarrays were constructed from tumor tissue samples from two cohorts including in total 536 patients (University Hospital of North Norway, n = 285; Nordland Hospital, n = 251) with primary resected stage I to IIIA NSCLC. The density of CD45RO+ and CD8+ TILs in tumor epithelial and stromal compartments of the tumors was evaluated by immunohistochemistry. In univariate analyses, intraepithelial CD45RO+ TIL density (T-CD45RO) was a significant prognostic factor for disease-specific survival (P = .007), limited to the squamous cell carcinoma (SCC) histology subgroup (P b .001), where it was significant in both cohorts (University Hospital of North Norway, P = .003; Nordland Hospital, P = .022). Combining T-CD45RO and stromal CD8+ TIL density (S-CD8) increased the prognostic impact in SCC (P b .001) and showed a significant impact within all pathological stages (I, P = .025; II, P b .001; III, P = .001). In the multivariate analysis, T-CD45RO was an independent positive prognostic factor for SCC (hazard ratio 2.65, 95% confidence interval 1.64-4.28, P b .001), and in combination with S-CD8, the prognostic impact increased vastly (high + high versus low + low: hazard ratio 6.50, 95% confidence interval 3.54-11.91, P b .001). In conclusion, T-CD45RO was an independent prognostic factor for SCC NSCLC. When combined with S-CD8, the prognostic impact increased and was significant within each pathological stage. We propose CD45RO as a candidate marker for TNM-Immunoscore in SCC NSCLC.